Metal pollution trajectories and mixture risk assessed by combining dated cores and subsurface sediments along a major European river (Rhône River, France). (November 2020) - Dendievel, André-Marie; Mourier, Brice; Dabrin, Aymeric; Delile, Hugo; Coynel, Alexandra; Gosset, Antoine; Liber, Yohan; Berger, Jean-François; Bedell, Jean-Philippe
Highlights: Joint analysis of dated cores and subsurface sediments to reconstruct pollution trends. Local geochemical backgrounds established from pre-industrial palaeochannel cores. Metal trajectories influenced by local hotspots and diffuse pollution until the 1990s. Sediment quality recovery varied from a metal to another and according to the location. High influence of some metals (e.g. Cu) in the risk of pollutant mixture. Abstract: In European rivers, research and monitoring programmes have targeted metal pollution from bed and floodplain sediments since the mid-20 th century by using various sampling and analysis protocols. We propose to characterise metal contamination trajectories since the 1960s based on the joint use of a large amount of data from dated cores and subsurface sediments along the Rhône River (ca. 512 km, Switzerland–France). For the reconstruction of spatio-temporal trends, enrichment factors (EF) and geo-accumulation (Igeo) approaches were compared. The latter index was preferred due to the recurrent lack of grain-size and lithogenic elements in the dataset. Local geochemical backgrounds were established near (1) the Subalps and (2) the Massif Central to consider the geological variability of the watershed. A high contamination (Igeo = 3–5) was found for Cd, Cu and Zn from upstream to downstream over the period 1980–2000. This pattern is consistent with long-term emissions from major cities and the nearby industrial areas of the Upper Rhône (Geneva, Arve Valley), and Middle Rhône (Lyon, Chemical Corridor, Gier Valley). Hotspots due to Cu and Zn leaching from vineyards, mining, and highway runoff were also identified, while Pb was especially driven by industrial sources. The recovery time of pollution in sediment varied according to the metals and was shorter upstream of Lyon (15–20 years) than downstream (30–40 years). More widely, it was faster on the Rhône than along other European rivers (e.g. Seine and Rhine). Finally, the ecotoxicological mixture risk of metal with Persistent Organic Pollutants (POPs) for sediment-dwelling organisms showed a medium "cocktail risk" dominated by metals upstream of Lyon, although it is enhanced due to POPs downstream, and southward to the delta and the Mediterranean Sea. Overall, this study demonstrates the heterogeneity of the contamination trends along large fluvial corridors such as the Rhône River.